A highly selective and light-up red emissive fluorescent probe for imaging of penicillin G amidase in Bacillus cereus. (5th April 2019) - Wang, Jianguo; Chen, Qingqing; Wu, Jie; Zhu, Wenping; Wu, Yongquan; Fan, Xiaolin; Zhang, Guanxin; Li, Yibao; Jiang, Guoyu
Abstract : A highly selective and red-emissive fluorescent probe (HCyNB ) for penicillin G amidase (PGA ) has been prepared and used for imaging of endogenousPGA in penicillinase-producing Bacillus subtilis . Abstract : A highly selective and red emissive fluorescent probe (HCyNB ) for penicillin G amidase (PGA ) has been prepared in a simple two-step process. After enzymatic reaction, HCyNB showed a fast response toPGA and afforded a light-up red fluorescence assay ofPGA with a detection limit of 0.067 U L −1, without interference from other biologically-relevant species and enzymes, including ROS. The easy synthesis, fast response, good sensitivity, remarkable selectivity and pH independence renderHCyNB an outstanding tool for bioimaging of endogenousPGA in penicillinase-producing Bacillus subtilis .